A pilot yoga physical education curriculum to promote positive body image. (December 2017) - Cox, Anne E.; Ullrich-French, Sarah; Howe, Holly S.; Cole, Amy N.
Highlights: Decreases in body surveillance were observed during a 12-week yoga curriculum. Increases in physical self-worth were observed during a 12-week yoga curriculum. Change in trait body surveillance inversely related to change in positive body image. State mindfulness inversely predicted state body surveillance during yoga classes. Cultivating mindfulness during yoga may support adolescent positive body image. Abstract: We examined the effects of a pilot yoga-based physical education (PE) curriculum by testing for change in trait body surveillance, physical self-worth, and body appreciation. Further, we examined the relationships among change in body image variables and the role of state mindfulness in predicting state body surveillance during classes. Adolescents participated in 12 weeks of yoga-based ( n = 20; M age = 16.45, 90% female) or traditional ( n = 23; M age = 14.52, 57% female) PE. Results showed significant ( p = .004), moderate decreases in trait body surveillance and minimal nonsignificant ( p = .11) increases in physical self-worth. Change in trait body surveillance was inversely related to change in physical self-worth and body appreciation in yoga participants. Multi-level modeling analyses revealed that more mindful students also surveyed their body less during class. Intentionally structured yoga participation may support positive body image among adolescents.